Can weblogs reduce writing anxiety and facilitate improvement in writing skills? - Cequena, Maria B. (Animo Repository, 2014)
Previous studies lack findings on how an instructional setting that utilizes CMC may both aid in the development of writing proficiency and reduce anxiety associated with the demands of writings. This pilot study attempts to fill this gap by investigating the effects of online portfolio through weblogs (blogging) on students' writing anxiety and writing skills. Seventeen (17) respondents enrolled in an English Communication course of a private university in the Philippines participated in the study. Data were gathered using Cheng's (2004) Second Language Writing Anxiety Inventory (SLWAI), Discourse Completion Task (DCT), focus group discussion (FGD), and content analysis of students' blog comments. Results of the questionnaire revealed that students with low, average, and high writing anxiety reported common causes of their writing anxiety such as limited vocabulary, difficulty in organizing their thoughts when asked to write under time pressure, and fear of students' and teacher's evaluations. Based on their DCT and FGD replies, blogging as improved their writing skills and as lessened their writing anxiety.